2004
DOI: 10.1158/1078-0432.ccr-03-0192
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Activation Mediates the Proangiogenic Effect of Nitric Oxide in Colorectal Cancer

Abstract: Purpose: Up-regulation of both inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) enzymes has been reported in colorectal cancer. We aimed at evaluating the possible interaction between the nitric oxide and COX-2 pathways, and its effect on promoting tumor angiogenesis.Experimental Design: Expression of iNOS, COX-2, vascular endothelial growth factor (VEGF), and CD31 was analyzed in tumor samples and corresponding normal mucosa obtained from 46 surgical specimens. We also evaluated iNOS activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 49 publications
5
83
0
2
Order By: Relevance
“…The absorbance of the organic phase was read spectrophotometrically at 532 nm wavelength over a standard curve of 1,1,3,3-tetramethoxypropane. The values are expressed as ng/mg of proteins, the latter determined as previously described [32].…”
Section: Determination Of Thiobarbituric Acid-reactive Substances (Tbmentioning
confidence: 99%
“…The absorbance of the organic phase was read spectrophotometrically at 532 nm wavelength over a standard curve of 1,1,3,3-tetramethoxypropane. The values are expressed as ng/mg of proteins, the latter determined as previously described [32].…”
Section: Determination Of Thiobarbituric Acid-reactive Substances (Tbmentioning
confidence: 99%
“…Prostaglandin E 2 (PgE 2 ) and Vascular Endothelial Growth Factor (VEGF) Production Supernatants (100 lL each) were utilized for PGE 2 and VEGF determination using competitive enzyme immunoassay kits (Cayman Chemical Co, Ann Arbor, MI, USA) according to methods previously described (Cianchi et al [8]). Celecoxib, 1 lmol/L, was added 30 min before adding EGF or DCA at 1 lM concentration.…”
Section: Cox-2 and Vegf Protein Expressionmentioning
confidence: 99%
“…COX-1 is considered a housekeeping gene and is constitutively expressed in most normal tissues, whereas COX-2 is an inducible enzyme, which can be rapidly induced by cytokines, inflammatory mediators, growth factors and tumour promoters and is related to human inflammatory diseases and carcinogenesis in different tissues [1][2][3][4][5]. A large body of evidence suggests that induction of COX-2 plays a pivotal role in cancer development by promoting cell proliferation, decreasing apoptosis rate, stimulating angiogenesis and increasing invasive and metastatic potential of the primary tumour [6][7][8][9]. A role of COX-2 in carcinogenesis is also indirectly supported by a wealth of epidemiological data which have shown an association of the long-term use of non steroidal anti-inflammatory drugs (NSAIDs) with a decreased incidence of colorectal, gastric and oesophageal cancers [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies with aberrant data (over a 10-fold difference than those reported in other papers) were also excluded. Based on these criteria, 12 studies were excluded from our collection (Liu et al, 1999;Haggstrom et al, 2000;Bhujwalla et al, 2001;Feldman et al, 2001;George et al, 2001;Huss et al, 2001;Kelavkar et al, 2001;Calvo et al, 2002;Mabjeesh et al, 2003;Cianchi et al, 2004;Singh et al, 2004;May et al, 2005) (Supplementary Table S6). …”
Section: Publication Selectionmentioning
confidence: 99%